The relationship between photo retouching addiction and social appearance anxiety for social internet users - Desheng Yan; Guangming Li; Guangming Li (Frontiers in Public Health)
There is a large population of social internet users who habitually retouch photos. These behaviors may be harmful, as some studies have shown that photo retouching behaviors may result in the potential risk of dependency and some addiction-like symptoms. Specifically, chronic photo retouching behaviors of social internet users can lead to negative emotions, low satisfaction with appearance, and non-essential cosmetic surgery. Severe cases may suffer from “Snapchat dysmorphia” which could become a form of body dysmorphic disorder. In this paper, the photo retouching addiction scale (PRAS) was developed as a psychometric instrument to measure the degree of photo retouching addiction for social internet users. Through a cross-sectional study, the social appearance anxiety scale (SAAS) was combined with the PRAS to investigate whether the relationship exists between photo retouching addiction and social appearance anxiety. Results show that: (1) The developed PRAS includes five dimensions and has good reliability and validity (Cronbach’s Alpha = 0.862; χ2/df = 1.511, CFI = 0.975, TLI = 0.968, RMSEA = 0.041, SRMR = 0.031); (2) The photo retouching addiction is significantly positively correlated with social appearance anxiety; (3) Sex, age, and marital status of social internet users have a significant impact between photo retouching addiction and social appearance anxiety.